A case of rheumatoid arthritis treated with infliximab who developed disseminated Penicillium marneffei infection after visit to Thailand. Issue 2 (3rd July 2017) - Yoshinari, Hiroko; Saito, Kazuyoshi; Nakano, Kazuhisa; Fukuyo, Shunsuke; Miyagawa, Ippei; Tanaka, Yoshiya
Abstract: We reported a case of Penicillium marneffei infection in a 56-year-old man who was being treated for rheumatoid arthritis (RA) since the year 2009 and had no history of corticosteroid treatment. In January 2012, he visited Thailand where he developed fever, general malaise and dyspnea. He immediately returned to Japan and was admitted to our hospital on the same day. On admission, the patient presented with dyspnea (pO2, 96 mmHg) while receiving oxygen (10 L/min) via a reservoir mask; liver enzyme, C-reactive protein (16.2 mg/dL) and β-d -glucan (42.2 pg/mL) levels were also elevated. Thoracoabdominal computed tomography showed diffuse micronodules in both lungs and hepatosplenomegaly. Round-to-oval, yeast-like fungi with central septum, phagocytosis and granuloma formation were observed in the liver and alveolar tissues. The patient was diagnosed with disseminated P. marneffei infection. Treatment with amphotericin B and micafungin was started, and the patient's general condition improved. Voriconazole was administered as maintenance therapy, and there was no relapse. Further, RA did not relapse despite the lack of RA treatment. P. marneffei infection is an opportunistic fungal infection endemic to Southeast Asian countries. In recent years, apart from HIV patients, P. marneffei infection has been reported in non-HIV immunocompromised patients as well. This is the first case of P. marneffei infection in a patient receiving RA treatment. Clinicians should be aware that patients on immunosuppressive therapy are at risk of P. marneffei infection.